REPETITION IN CHILD-DIRECTED QUESTIONS; A COMPARISON OF TURKISH AND ENGLISH LANGUAGES - Ilhan, Berk (My University, 2019)
The studies for repetition in Child-directed Speech (CDS) have focused mostly on affirmative andnegative sentences without discrimination and the children in these studies have been the ones who canproduce one or two words. There is a gap in the field of Turkish language acquisition for studies whichanalyze speech directed to children at earlier ages. In order to contribute to the field, the present study hasinvestigated if there are common variation sets in child-directed Turkish questions at early ages or not andwhether there are different variation sets in English and Turkish questions. As Turkish data, theconversations between Eylül (1:3) and her caregivers have been recorded for two months by the researcherand English data (Morgan, 1:3) has been obtained from CHILDES database. The analysis has revealed thataddition of specific reference and reordering are the most common variation sets in Turkish questions.However, in English questions, the most common sets are lexical substitution, rephrasing and deletion ofspecific reference. Child directed questions in English tend to be economical, whereas, Turkish questionsprovide more cues about the structure of language by presenting them to the child by repetition.
Keywords: Dil ve Dil Bilim